Getting Old through the Blood: Circulating Molecules in Aging and Senescence of Cardiovascular Regenerative Cells - Angelini, Francesco; Pagano, Francesca; Bordin, Antonella; Picchio, Vittorio; De Falco, Elena; Chimenti, Isotta (Frontiers in Cardiovascular Medicine, 2017)
Global aging is a hallmark of our century. The natural multifactorial process resulting in aging involves structural and functional changes, affecting molecules, cells, and tissues. As the western population is getting older, we are witnessing an increase in the burden of cardiovascular events, some of which are known to be directly linked to cellular senescence and dysfunction. In this review, we will focus on the description of a few circulating molecules, which have been correlated to lifespan, aging, and cardiovascular homeostasis. We review the current literature concerning the circulating levels and related signalling pathways of selected proteins (IGF-1, GDF-11 and PAI-1) and microRNAs of interest (miR-34a, miR-146a, miR-21) whose bloodstream levels have been associated to aging in different organisms. In particular, we also discuss their potential role in the biology and senescence of cardiovascular regenerative cell types, such as endothelial progenitor cells, mesenchymal stromal cells, and cardiac progenitor cells.